2014
DOI: 10.1038/srep04286
|View full text |Cite
|
Sign up to set email alerts
|

Genomics In Premature Infants: A Non-Invasive Strategy To Obtain High-Quality DNA

Abstract: We used a cost-effective, non-invasive method to obtain high-quality DNA from buccal epithelial-cells (BEC) of premature infants for genomic analysis. DNAs from BEC were obtained from premature infants with gestational age ≤ 36 weeks. Short terminal repeats (STRs) were performed simultaneously on DNA obtained from the buccal swabs and blood from the same patient. The STR profiles demonstrated that the samples originated from the same individual and exclude any contamination by external DNAs. Whole exome sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…First, the swab, lasting seconds, is much less stressful than a painful needle prick to obtain peripheral blood, and this stress might influence methylation in itself. Second, this approach provides a more direct comparison with human studies where ethical reasons preclude needle pain, although buccal swabs are routinely implemented (20, 21). Finally, several studies found that DNA methylation profiles in buccal swab cells are more similar to patterns from several brain regions than methylation profiles in WBCs (21, 22, 23, 24).…”
Section: Resultsmentioning
confidence: 99%
“…First, the swab, lasting seconds, is much less stressful than a painful needle prick to obtain peripheral blood, and this stress might influence methylation in itself. Second, this approach provides a more direct comparison with human studies where ethical reasons preclude needle pain, although buccal swabs are routinely implemented (20, 21). Finally, several studies found that DNA methylation profiles in buccal swab cells are more similar to patterns from several brain regions than methylation profiles in WBCs (21, 22, 23, 24).…”
Section: Resultsmentioning
confidence: 99%
“…Cytological brushes were used to swab the buccal mucosa and obtain neonatal DNA using methodology previously validated by our group 27 . Enrolled subjects were nil per os (NPO) at the time of buccal swab collection.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from buccal swab specimens using Qiagen Buccal Cell Kit (Qiagen Sciences, Germantown, MD). The buccal cell extraction kit was modified for a cell lysate volume of 900μl 27 . After cell lysis, genomic DNA was extracted with 5 μl proteinase k and isopropanol/ethanol precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Our study has demonstrated that HRM genotyping of DNA material derived from buccal swab yielded satisfactory and reliable results. A study which also employed buccal swab sampling indicated that buccal epithelial cells provided a reliable source of DNA and promising results were obtained from genetic analysis such as short tandem repeat analysis, Taqman allelic discrimination assay, PCR-restriction fragment length polymorphism (PCR-RFLP) and whole exome sequencing (Said et al, 2014).…”
Section: Discussionmentioning
confidence: 99%